Student’s Satisfaction with Online Teaching during the COVID-19 Pandemic - Uzma Ahsan, Ahsan Nasim, Aqsa Aslam, Farooq Azam Khan, Maria Aslam, Lamia Yusuf (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: This study was conducted to determine the level of student’s satisfaction with online teaching during the COVID-19 pandemic. Methodology: The study was conducted in Sharif Medical and Dental College, Lahore from 10th June to 10th July 2020. It was a cross-sectional survey in which MBBS and BDS students were consecutively enrolled in the study. An online survey was carried out after the completion of 6 weeks of online classes through the Zoom application. A self-designed questionnaire based on a 5-point Likert scale was given to the students to grade the effectiveness of learning through e-classes and their satisfaction level on various parameters. On the Likert scale, 1 & 2 were taken as highly dissatisfied (strongly disagree, &disagree) and 4 & 5 being satisfied (strongly agree, & agree) and 3 was considered as uncertain. Percentages of the respondents in each domain of the questionnaire were calculated. Results: Out of 470 participants, only 72(15.32%) students already had an experience of e-classes. Among the study participants, 327(69.57%) were of MBBS and 143(30.43%) were of BDS. The majority of the students 291(61.91%) were not satisfied with online classes, 99(21.06%) of students were uncertain and only 80(17.02%) of the students were satisfied. Conclusion: The majority of the students 291(61.91%) were not satisfied with online classes in terms of learning environment, technological characteristics, and course management.